Application of phytoremediation on treating palm oil mill final discharge water / Mohamad Efzal Mohd Rais - Mohd Rais, Mohamad Efzal (Faculty of Plantation and Agrotechnology, 2019)
The application of the phytoremediation on treating palm oil mill final discharge essentially should give a good impression to the condition of the downstream water content. The different type of the aquatic life applied give the different result to the downstream water content. Other than application of the remediation has been proved faster affect and result nevertheless they had a couple of problems. So as the other alternative is natural application such as phytoremediation can help the palm oil mill industry to treat the effluent from the mill naturally. This experiment was conducted to observe the consequences of the POME condition by applying different type of aquatic plant. The sample of the pome was collected at downstream stages of the palm oil mill effluent. Then experiment was conducted at irrigation workshop UiTM Jasin. Data collected was done every day for the parameter of pH, total dissolve solid, salinity, dissolve oxygen, percentage dissolve oxygen, conductivity and turbidity within the 15 days. Data analysis was conducted using the SPSS and the Microsoft Excel application. The results obtained in this study indicate that the quantity of aquatic plant and the type of aquatic life applied is still compatible for treating the downstream water from the palm oil mill final discharge.